PENERAPAN MODEL KOOPERATIF LEARNING TIPE PICTURE AND PICTURE UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV SDN 04 PULAU PUNJUNG - 27Maitri Alkautsar18 (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dharmas Indonesia, 2025)
This study aims to improve the learning interest of fourth grade students of SDN 04 Pulau Punjung through the application of the cooperative learning model type picture and picture. The problem found in the learning process is the lack of variation in methods used by teachers, so that students become passive and less interested in the subject matter. This study uses an action research approach (PTK) with two cycles consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were 34 fourth grade students of SDN 04 Pulau Punjung. Data collection techniques were carried out through observation, non-tests, field notes, and the data that had been collected was analyzed using qualitative descriptive analysis techniques. The results of the study showed that the application of the picture and picture model can increase students' interest in learning, students become more active, and students' understanding of the material increases.